Perkembangan Yayasan Liga Dakwah Sumatera Barat: Studi Sejarah Lembaga 1988-2025 - Taufik Hidayat; Hendra Naldi (Jurusan Sejarah FIS UNP, 2026)
This study examines the institutional development of the West Sumatra Liga Dakwah Foundation from 1988 to 2025. The research is important because the foundation's transformation from a preacher-cadre initiative into an integrated institution managing a girls' junior high school, senior high school, orphanage, and boarding facility has not been systematically documented. Using the historical method, the study applied heuristics, source criticism, interpretation, and historiography to institutional archives, legal documents, school records, photographs, observations, and interviews. The findings show that the foundation was legally established on 3 October 1988 and initially focused on Islamic preaching cadre development. The arrival of fifteen Muslim-convert children from the Mentawai Islands encouraged a shift toward boarding education for girls. The senior high school developed during 1996-1997, the orphanage was established in 1999, land acquisition and construction occurred in 2004-2005, and the junior high school opened in 2009. By 2025, the foundation had integrated formal education, religious formation, residential care, discipline, and life-skills training. Its continuity depended on committed administrators, community networks, donors, government support, and alumni, although funding, facilities, documentation, and managerial regeneration remained major constraints.